The Polish Enlightenment Poetry in the Kharkiv Periodicals and Books between 1819 and 1820 - Magdalena Dabrowska (Zeszyty Cyrylo-Metodiańskie)
The paper presents the reception of the Polish Enlightenment poetry in the Russian-language periodicals (monthly ‘Ukrainski Vestnik’, 1816–1819) and books (a volume of poetry ‘The Attempts in Verses’ by Aleksander Skłabowski, 1819; a collection ‘The Works and Translations by the Students of the Imperial University in Kharkiv...’, 1820), published by the Kharkiv University Publishing House in the first half of the 19th century. The methods employed in the research are bibliographic heuristics, comparative literature and translation studies. The paper consists of three parts: the outline of history of the Polish Language Department and publishing at the Kharkiv University; the register of the free translations and imitations of the works by the Polish poets (Franciszek Karpiński and Adam Naruszewicz); the comparison of Naruszewicz’s poem ‘To the Stream’ (1771) with Aleksandr Sklabovskij’s poem ‘To the Stream’ (1819). The interest in Polish history and literature in Kharkiv was strongly influenced by the work performed at the Polish Language Department at Kharkiv University since 1818. Original title in Polish: Polska poezja oświeceniowa w charkowskich wydawnictwach periodycznych i książkowych z lat 1819–1820